From Inside the Rhizome: Mapping the Greek Alternative Mediascape - Milioni, Dimitra L.; Vatikiotis, Pantelits (My University, 2019)
We use the rhizome metaphor to approach the highly elusive and contingent field of alternative media. We explore the multiplicity of alternative media practices employed by diverse social actors, critically reflecting on the rhizome’s capacity to foster cooperation and synergy, building alliances. At the empirical level, the article maps the Greek alternative mediascape; highlights the multiple paths that lead participants into it and explains the heterogeneity of the field; evaluates the diverse ways in which alternative media projects challenge hegemonic power; and explores connections within the alternative mediascape, revealing the presence of both cooperation/solidarity and isolationism/fragmentation. Last, we discuss how these findings feed back into the concept of the rhizome in the context of alternative media.
Keywords: alternative media; rhizome; hegemony; ideology; Greece